‘The Telepsychiatry Clinic On-the-Run’: How a Unique Tele-Mental Health Clinic Is Thriving in the Midst of Political Turmoil in Myanmar - Nilar Thwin; Khin May Lwin; Paing Soe; Yan Lin Aung; Ei Thin Zar Thwe (BJPsych Open)
Aims: The WHO estimated that 1 in 5 people living in conflict areas have some form of mental disorder. On top of this, limited access to mental health care in these areas continues to amplify the issue. However, hope can be found through the increased use of telehealth during the COVID-19 pandemic, which has opened the opportunity to apply the platform in conflict zones.